The approach to a HIV infected patient in view of legal regulations - Mikołajczyk, Katarzyna; Żaba, Czesław; Bujny, Jędrzej; Żaba, Ryszard (Przewodnik Lekarza/Guide for GPs, 2005)
The first cases of a disease named later Acquired Immunodeficiency Syndrome AIDS were observed in 1981 in United States. It is estimated that from that time 33.6 million people worldwide have been infected with HIV virus. As time went by the negative emotions associated with the disease in general public have lessened. AIDS in medical and legal view is a disease like any other diseases, that the medicine tries to combat, and the people with acquired immune deficiency are protected by common law. However the specificity of HIV infection, and the consequences attributed to this infection, call for an additional legal regulations especially in everyday life and also handling of those patients by doctors. The aim of this paper was to acquaint the reader with present state of legal regulations as far as the approach to a patient suspected of having HIV infection or with one known to have HIV infection. The legal aspects of preserving the confidentiality of a patient-doctor relationship, and also some circumstances which release the doctor from keeping the secret. Also some controversial aspects of caring for patients with HIV and AIDS, and the span of liability for declining the care to such patients.